Trends in epilepsy surgery: stable surgical numbers despite increasing presurgical volumes. Issue 12 (5th October 2016) - Cloppenborg, Thomas; May, Theodor W; Blümcke, Ingmar; Grewe, Philip; Hopf, Lena J; Kalbhenn, Thilo; Pfäfflin, Margarete; Polster, Tilman; Schulz, Reinhard; Woermann, Friedrich G; Bien, Christian G
Abstract : Introduction: Despite the success of epilepsy surgery, recent reports suggest a decline in surgical numbers. We tested these trends in our cohort to elucidate potential reasons. Patients and methods: Presurgical, surgical and postsurgical data of all patients undergoing presurgical evaluation in between 1990 and 2013 were retrospectively analysed. Patients were grouped according to the underlying pathology. Results: A total of 3060 patients were presurgically studied, and resective surgery was performed in 66.8% (n=2044) of them: medial temporal sclerosis (MTS): n=675, 33.0%; benign tumour (BT): n=408, 20.0%; and focal cortical dysplasia (FCD): n=284, 13.9%. Of these, 1929 patients (94.4%) had a follow-up of 2 years, and 50.8% were completely seizure free (Engel IA). Seizure freedom rate slightly improved over time. Presurgical evaluations continuously increased, whereas surgical interventions did not. Numbers for MTS, BT and temporal lobe resections decreased since 2009. The number of non-lesional patients and the need for intracranial recordings increased. More evaluated patients did not undergo surgery (more than 50% in 2010–2013) because patients were not suitable (mainly due to missing hypothesis: 4.5% in 1990–1993 up to 21.1% in 2010–2013, total 13.4%) or declined from surgery (maximum 21.0% in 2010–2013, total 10.9%). One potential reason may be that increasingly detailed information on chances and risks were given over time. Conclusions: The increasing volume of the presurgical programme largely compensates for decreasing numbers of surgically remediable syndromes and a growing rate of informed choice against epilepsy surgery. Although comprehensive diagnostic evaluation is offered to a larger group of epilepsy patients, surgical numbers remain stable.